2016
DOI: 10.1002/adma.201505345
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Two‐Dimensional Transition‐Metal Dichalcogenides

Abstract: Two-dimensional (2D) layered transition metal dichalcogenides (TMDs) are a fascinating class of nanomaterials that have the potential for application in catalysis, electronics, photonics, energy storage, and sensing. TMDs are rather inert, and thus pose problems for chemical derivatization. However, to further modify the properties of TMDs and fully harness their capabilities, routes towards their chemical functionalization must be identified. In this research news article we critically review recent efforts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
177
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(187 citation statements)
references
References 49 publications
1
177
0
Order By: Relevance
“…In monolayer MoS 2 (thickness ≈0.6 nm), the band gap becomes direct with a width of 1.8 eV. [1] Importantly, to meet the requirements of different applications, properties of MoS 2 and other TMDCs can be tuned by controlling the thickness, [1] doping and alloying, [5][6][7][8] surface modification and functionalization, [9][10][11] strain, [12,13] and by creating heterostructures with other 2D materials. [6,[14][15][16] The appealing properties of TMDCs have led to a wide range of proposed applications.…”
Section: Doi: 101002/admi201700123mentioning
confidence: 99%
“…In monolayer MoS 2 (thickness ≈0.6 nm), the band gap becomes direct with a width of 1.8 eV. [1] Importantly, to meet the requirements of different applications, properties of MoS 2 and other TMDCs can be tuned by controlling the thickness, [1] doping and alloying, [5][6][7][8] surface modification and functionalization, [9][10][11] strain, [12,13] and by creating heterostructures with other 2D materials. [6,[14][15][16] The appealing properties of TMDCs have led to a wide range of proposed applications.…”
Section: Doi: 101002/admi201700123mentioning
confidence: 99%
“…[17][18][19] Secondly, chemical functionalisation to further tailor the materials' properties on demand is currently in its infancy. [20][21][22] With few exceptions, 23,24 the covalent chemistry is currently limited to CE-1T-TMDs, which are of less interest in optoelectronic applications due to its lack of visible optical absorption or emission. In addition to the functionalisation routes involving the addition of organic molecules, 20,21 it has been shown that CE-1T-TMDs react with AuCl 3 even in the absence of additional reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] With few exceptions, 23,24 the covalent chemistry is currently limited to CE-1T-TMDs, which are of less interest in optoelectronic applications due to its lack of visible optical absorption or emission. In addition to the functionalisation routes involving the addition of organic molecules, 20,21 it has been shown that CE-1T-TMDs react with AuCl 3 even in the absence of additional reducing agents. [25][26][27][28] As a result, Au 0 is produced and nucleates to form Au nanoparticles (AuNPs).…”
Section: Introductionmentioning
confidence: 99%
“…

biomedicine, [2,3] tribology, [4] photonics, [5] and electrocatalysis, [6] among others. [7] This progress has focused on the functionalization of mono-or few-layer nanosheets with lateral dimensions greater than 100 nm by combining chemical exfoliation, [8][9][10][11][12] micromechanical exfoliation, [13] or liquid exfoliation [14] with the reaction of functionalities. [7] This progress has focused on the functionalization of mono-or few-layer nanosheets with lateral dimensions greater than 100 nm by combining chemical exfoliation, [8][9][10][11][12] micromechanical exfoliation, [13] or liquid exfoliation [14] with the reaction of functionalities.

…”
mentioning
confidence: 99%